Rheology of a nematic active suspension undergoing oscillatory shear and step strain flows - Malvar, Sara; Souza Carmo, Bruno; R. Cunha, F. (Rheologica Acta, 2019)
We investigate experimentally the rheology of an active suspension of nematodes C. elegans under oscillatory shear. There are few experimental investigations and theoretical work on the oscillatory rheological properties including elastic and viscous moduli of micro-swimmer suspensions. The viscous and elastic moduli are evaluated by our experiments in the regime of linear viscoelasticity. These viscoelastic quantities are explored at low frequency given the active suspension viscosity and the shear elastic modulus. The experiments have revealed an anomalous behavior of the viscosity and the shear elastic modulus with the variation of the suspension volume fraction. The suspension relative viscosity decreased with the increase of active particles within a certain range of volume fraction. However, above a critical particle volume fraction, the relative viscosity increases. This observed increase of the viscosity for larger concentration is a direct consequence of formation of large and coherent oriented structures and active particle interactions. This collective behavior also increases the first normal stress difference N1, obtained through Cox–Merz rule. Three different regions are obtained regarding different involved mechanisms and a physical interpretation is provided based on the particles dipole stresslet. Step strain tests are carried out and the active relaxation time as a function of volume fractions are obtained. An intrinsic oscillatory behavior is observed regardless the volume fraction, showing the non-equilibrium condition of the active suspension.